Analysis of volatility characteristics of five jujube varieties in Xinjiang Province, China, by HS‐SPME‐GC/MS and E‐nose. Issue 12 (29th September 2021) - Liu, Yuxing; Sang, Yueying; Guo, Jingyu; Zhang, Weida; Zhang, Tianyu; Wang, Hai; Cheng, Shaobo; Chen, Guogang
Abstract: In this study, headspace solid‐phase microextraction coupled with gas chromatography‐mass spectrometry (HS‐SPME‐GC/MS) was used to identify individual volatile compounds in five jujube varieties, and E‐nose was used to identify their flavor. The results showed that a total of 45 volatile compounds were detected by GC‐MS in the five varieties, and the proportion of acids was the highest (38.29%–54.95%), followed by that of aldehydes (22.94%–47.93%) and esters (6.33%–26.61%). Moreover, different varieties had obviously different volatile components. E‐nose analysis showed that the R7 and R9 sensors were more sensitive to the aroma of jujube than other sensors. The strong response of R7 sensor was attributed to terpenes (or structurally similar substances) in jujube fruit, such as 1‐penten‐3‐one, 2‐octenal, (E)‐2‐heptanaldehyde, and (E)‐2‐hexenal and that of R9 sensor was attributed to the cyclic volatile components such as benzaldehyde, benzoic acid, and methyl benzoate. The multivariate data analysis (PCA, OPLS‐DA, and HCA) of the results of GC/MS and E‐nose showed that the five varieties could be divided into three groups: (1) Ziziphus jujuba Mill. cv. Huizao (HZ) and Z. jujuba cv. Junzao (JZ). Acids were the main volatile components for this group (accounting for 47.44% and 54.95%, respectively); (2) Z. jujuba cv. Hamidazao (HMDZ). This group had the most abundant volatile components (41), and the concentrations were also the highest (1285.43 µg/kg); (3) Winter jujube 1 ( Z . jujuba cv. Dongzao, WJ1) and Winter jujube 2 ( Z . jujuba cv. Dongzao, WJ2). The proportion of acids (38.38% and 38.29%) and aldehydes (40.35% and 38.19%) were similar in the two varieties. Therefore, the combination of headspace solid‐phase microextraction coupled with gas chromatography‐mass spectrometry and E‐nose could quickly and accurately identify the volatile components in jujube varieties from macro‐ and microperspectives. This study can provide guidance for the evaluation and distinguishing of jujube varieties and jujube cultivation and processing. Abstract : The volatile components of fruits of five jujube varieties cultivated in Xinjiang Province, China, were analyzed using the HS‐SPME‐GC/MS and E‐nose. GC‐MS and E‐nose results were separated by multivariate analysis. This study provides guidance for the selection of raw materials and jujubes processing.